1991
DOI: 10.1073/pnas.88.20.9046
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sleep in rats by inorganic selenium compounds, inhibitors of prostaglandin D synthase.

Abstract: Prostaglandin (PG) D2 has been postulated to be an endogenous sleep-promoting factor in rats, and SeC14 and Na2SeO3 recently have been shown to inhibit the PGD synthase (prostaglandin-H2 D-isomerase, EC 5.3.99.2) activity of rat brain. The effect of these selenium compounds on sleep-wake activities was examined in freely moving rats along with their effects on brain temperature, food and water intake, and behavior. Test substances were administered for 6 hr into the third ventricle of rats, using a microdialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 23 publications
1
36
0
1
Order By: Relevance
“…Infusion of selective inhibitors of PGDS, e.g., tetravalent selenium compounds, reversibly, timeand dose-dependently inhibited both non-rapid eye movement (NREM) and rapid eye movement (REM) sleep during the daytime (13). These observations clearly showed that PGDS plays a crucial role in the regulation of physiological sleep.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Infusion of selective inhibitors of PGDS, e.g., tetravalent selenium compounds, reversibly, timeand dose-dependently inhibited both non-rapid eye movement (NREM) and rapid eye movement (REM) sleep during the daytime (13). These observations clearly showed that PGDS plays a crucial role in the regulation of physiological sleep.…”
mentioning
confidence: 57%
“…Previously, the relationship between PGD 2 and sleep was examined mainly pharmacologically by administration of exogenous PGD 2 into the brain and inhibition of PGDS in vivo by selenium compounds (3,4,10,13) or under certain pathological conditions as reported in some sleep disorders (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…PGD 2 -induced sleep was indistinguishable from natural physiological sleep as judged by several electrophysiological and behavioral criteria (5). Subsequent studies have shown that PGD 2 is involved in both circadian (6,7) and homeostatic regulation of sleep (8). Further studies on the molecular mechanisms of sleep-wake regulation by PGD 2 demonstrated that PGD 2 is produced by the action of lipocalin-type PGD synthase dominantly expressed in the leptomeninges (9), binds with PGD receptors (DPRs) exclusively localized in the arachnoid membrane of the basal forebrain (BF) (10), and promotes sleep through adenosine acting at adenosine A 2A receptors (A 2A R's) (11), followed by activation of sleep-active neurons in the ventrolateral preoptic (VLPO) area (12,13).…”
mentioning
confidence: 99%
“…Statistics was performed by use of paired t test, with each animal serving as its own control. Details of the scoring method of sleep-wake stages and the experimental equipments were described previously (2,15,16 (Fig. 1B), SWS showed a tendency to decrease during the first 3 hr of the infusion, but it then increased during the last 1-2 hr.…”
mentioning
confidence: 99%